Response of Finger Millet to Inorganic Fertilizers under Dolakha Condition of Nepal - Baral, Bandhu Raj; Subedi, Subash; Adhikari, Jagat Bandhu; Gurung, Suk Bahadur; Dhami, Narayan Bahadur (Journal of Nepal Agricultural Research Council, 2024)
A field experiment was carried out during 2020, 2021 and 2022 to study the response of finger millet on fertilizer doses at Hill Crops Research Program, Kabre, Dolakha. The field experiment consists of seven fertilizer treatments with different nutrient combination doses, replicated thrice and laid out in randomized complete block design. The tested variety was Kabre Kodo-2. Seven fertilizer treatments were 5 t FYM /ha (farmers practice), 30:30:30 N:P2O5:K2O kg/ha, 30:60:30 N:P2O5:K2O kg/ha, 60:30:30 N:P2O5:K2O kg/ha, 60:60:30 N:P2O5:K2O kg/ha, 90:30:30 N:P2O5:K2O kg/ha and 90:60:30 N:P2O5:K2O kg/ha, respectively. The results of the experiment showed that grain yield, stover yield and number of heads/m2were significantly affected by fertilizer doses (p<0.05). Kabre Kodo-2 variety of finger millet produced the highest grain yield (4.98 t/ha) and straw yield (8.27 t/ha) with the application 90:60:30 N:P2O5:K2O kg/ha and was at par with 60:30:30 N:P2O5:K2O kg/ha, 90:30:30 N:P2O5:K2O kg/ha and 60:60:30 N:P2O5:K2O kg/ha. These results clearly indicated that 60:30:30 N:P2O5:K2O kg/ha could be recommended for finger millet cultivation under Dolakha condition and in areas with similar soil types and ecology of Nepal.